ESX-5-targeted export of ESAT-6 in BCG combines enhanced immunogenicity & efficacy against murine tuberculosis with low virulence and reduced persistence - Heijmenberg, Isis; Husain, Aliabbas; Sathkumara, Harindra D.; Muruganandah, Visai; Seifert, Julia; Miranda-Hernandez, Socorro; Kashyap, Rajpal Singh; Field, Matt A.; Krishnamoorthy, Gopinath; Kupz, Andreas (Vaccine, 2021)
Tuberculosis (TB) is the leading infectious cause of death globally. The only licensed TB vaccine, Bacille Calmette–Guérin (BCG), has low efficacy against TB in adults and is not recommended in people with impaired immunity. The incorporation of the Mycobacterium tuberculosis (Mtb) secretion system ESX-1 into BCG improves immunogenicity and protection against TB in animal models, which is associated with the secretion of the ESX-1-dependent protein ESAT-6. However, the resulting strain, BCG::ESX1Mtb, has been deemed unsafe as a human vaccine, due to prolonged persistence and increased virulence in immunocompromised mice. In this study, we describe a new recombinant BCG strain that uncouples the beneficial aspects of ESAT-6 secretion from the detrimental ESX-1effects on virulence and persistence. The strain was constructed by fusing the ESAT-6-encoding gene esxA to the general secretion signal for the mycobacterial type VII secretion pathway protein PE25. This new strain, BCG::ESAT6-PE25SS, secretes full-length ESAT-6 via the ESX-5 secretion system, which in contrast to ESX-1 is also present in BCG. In vivo testing revealed that ESX-5-targeted ESAT-6 export, induces cytosolic contact, generates ESAT-6-specific T cells and enhances the protective efficacy against TB disease, but is associated with low virulence and reduced persistence in immunocompetent and immunocompromised mice. Additionally, compared to BCG::ESX1Mtb and parental BCG, mucosal administration of BCG::ESAT6-PE25SS is associated with more rapid clearance from the lung. These results warrant further studies to evaluate BCG::ESAT6-PE25SS as a potential live attenuated vaccine candidate for TB.